2013
DOI: 10.1107/s1600536813008325
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 2-oxo-3-(3-phthalimidopropyl)-2,3-dihydro-1H-1,3-benzimidazole-1-carboxylate

Abstract: In the title compound, C21H19N3O5, the phthalimide and benzamidazole ring systems are linked by a propyl chain. The benzamidazole unit also carries an eth­oxy­carbonyl substit­uent. The phthalimido and benzimidazole ring systems are essentially planar, the maximum deviations from their mean planes being 0.008 (2) and 0.020 (2) Å, respectively. The two ring systems are almost orthogonal to one another, making a dihedral angle of 82.37 (8)°. In the crystal, C—H⋯O hydrogen bonds and C—H⋯π contacts stack the mol­e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In continuation of our research work devoted to the development of substituted benzimidazol-2-one derivatives (Belaziz et al, 2012(Belaziz et al, , 2013, we reported a synthesis of new benzimidazol-2-one derivative differently substituted by action of allylbromide with 1-benzyl -1H-benzo[d]imidazol-2(3H)-one in the presence of a catalytic quantity of tetra-n-butylammonium bromide under mild conditions to obtain disubstituted compound (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuation of our research work devoted to the development of substituted benzimidazol-2-one derivatives (Belaziz et al, 2012(Belaziz et al, , 2013, we reported a synthesis of new benzimidazol-2-one derivative differently substituted by action of allylbromide with 1-benzyl -1H-benzo[d]imidazol-2(3H)-one in the presence of a catalytic quantity of tetra-n-butylammonium bromide under mild conditions to obtain disubstituted compound (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
“…For their use as intermediates in chemical synthesis, see: Bai et al (2001). For similar compounds, see: Belaziz et al (2012Belaziz et al ( , 2013.…”
Section: Related Literaturementioning
confidence: 99%
“…As a continuation of our research work devoted to the development of substituted benzimidazol-2-one derivatives [13][14][15], here we report on the synthesis of a new benzimidazol-2-one derivative displaying a new substitution pattern.…”
Section: Introductionmentioning
confidence: 99%